Gendered Punishment Practices Performed on Female Adolescents in their Passage through the Uruguayan Juvenile Justice System - López-Gallego, Laura (Oñati Socio-Legal Series, 2020)
This article is based on two research studies conducted on the Uruguayan Juvenile Justice System (UJJS); the first study (2011) examined female adolescent incarceration contexts, and the second one (2016) focused on female adolescents in their passage through a program of non-custodial measures. This research is aimed at understanding gendered punishment practices performed on women who are subjected to judicial measures in the UJJS, in order to give visibility to an issue that is usually silenced, among other reasons because the number of women subjected to these measures is low and due to a hegemonic male model in adolescent offense construction. Following a qualitative methodology research, combined with an ethnographic approach, I discuss the singularities characterizing the passage of female adolescents through the UJJS, by applying two strategies: (re)constructing a lost domesticity and managing bodies and sexualities.